2014
DOI: 10.1267/ahc.13038
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril-Associated Glycoprotein-1 Controls Human Ciliary Zonule Development <i>In Vitro</i>

Abstract: The ciliary zonule in the eye, also known as Zinn’s zonule, is composed of oxytalan fibers, which are bundles of microfibrils consisting mainly of fibrillin-1. However, it is still unclear which of the microfibril-associated molecules present in the ciliary zonule controls oxytalan fibers. Microfibril-associated glycoprotein-1 (MAGP-1) is the only microfibril-associated molecule identified in the human ciliary zonule. In the present study, we used siRNA against MAGP-1 in cultures of human non-pigmented ciliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We were therefore curious whether this system extends to the lens. We co-immunostained sections from adult eyes of normal and N-cad Δlens mice using antibodies to lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1), which is expressed by lymphatic endothelial cells and typically used to detect lymphatic vessels 58 , 59 , and MAGP1, a microfibrillar protein component of the ciliary zonules, the suspensory ligaments that connect the lens to the ciliary body 60 62 . We discovered that LYVE-1 positive labeling was closely aligned along MAGP1-positive suspensory ligaments in lenses from both wildtype and N-cad Δlens eyes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We were therefore curious whether this system extends to the lens. We co-immunostained sections from adult eyes of normal and N-cad Δlens mice using antibodies to lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1), which is expressed by lymphatic endothelial cells and typically used to detect lymphatic vessels 58 , 59 , and MAGP1, a microfibrillar protein component of the ciliary zonules, the suspensory ligaments that connect the lens to the ciliary body 60 62 . We discovered that LYVE-1 positive labeling was closely aligned along MAGP1-positive suspensory ligaments in lenses from both wildtype and N-cad Δlens eyes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 There is a fibrillin-binding domain in the carboxyl-terminal region of MFAP2, which contains 13 cysteine residues and binds MFAP2 to the extracellular matrix and an acidic amino-terminal region containing a growth factor interaction motif capable of interacting with the active form of transforming growth factor beta (TGF-β), but not with the latent form of the growth factor. 10 , 11 MFAP2 plays an important role in the extracellular deposition of fibrillin-1 during development of the human ciliary zonule, 12 and an in vivo study found that MFAP2 plays a key role in hemostasis and thrombosis because MFAP2-deficient mice showed delayed thrombotic occlusion of the carotid artery following injury, prolonged bleeding, and lower platelet number. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The main role of zonules is to maintain the lens in the center of the visual pathway and transmit contraction forces from ciliary bodies to the lens for accommodation. 26,27 Zonules can be classified into three subgroups: anterior, equatorial, and posterior parts based on the attachment point of these fibers on the lens. 28 Reduction in tensile strength of ciliary zonules or rupture of any fibers in any subgroup can weaken traction force to the lens.…”
Section: Discussionmentioning
confidence: 99%